2003
DOI: 10.1007/s11910-003-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Medication-induced peripheral neuropathy

Abstract: Although not very common, medication-induced neuropathy is a treatable condition and, therefore, is important to identify. Medications continue to grow in number and expand in usage; consequently, toxic neuropathy continues to be relevant to neurologists. Many agents have toxicities that are tolerated because the treatments are necessary, such as therapies for HIV and malignancy. Additional agents to prevent or ameliorate the toxic neuropathy are being sought and trials are ongoing. Certain patients, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
35

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 51 publications
1
31
0
35
Order By: Relevance
“…Our study also supports the dose-effect relationship based on the electrodiagnostic data and shows that more severe polyneuropathy is associated with receiving a higher cumulative dose of taxanes. Besides the dose-related factors, studies have also reported that the incidence of paclitaxel-induced neuropathy is affected by other factors including age (Akerley et al, 2003), diabetes (Gogas et al, 1996), and genetic predispositions (Aplenc et al, 2003;Wang et al, 2002;Wang et al, 2001;Weimer, 2003). We are not able to explore these correlations here because of the limited sample size.…”
Section: Discussionmentioning
confidence: 90%
“…Our study also supports the dose-effect relationship based on the electrodiagnostic data and shows that more severe polyneuropathy is associated with receiving a higher cumulative dose of taxanes. Besides the dose-related factors, studies have also reported that the incidence of paclitaxel-induced neuropathy is affected by other factors including age (Akerley et al, 2003), diabetes (Gogas et al, 1996), and genetic predispositions (Aplenc et al, 2003;Wang et al, 2002;Wang et al, 2001;Weimer, 2003). We are not able to explore these correlations here because of the limited sample size.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, the endoneural compartment lacks lymphatic system to remove toxins. 9 These factors increase the peripheral nerve vulnerability to potentially toxic medications as compared to the central nervous system. There is also evidence that chemotherapy drugs may directly damage the structure of the DRG cells and peripheral nerves that cause degeneration of sensory fibers or loss of small nerve fibers in the epidermal layer.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic traits are known to affect peripheral nerve vulnerability to toxins. Examples include the slow Wallerian degeneration (Wld S ) trait, which blunts the effects of axotomy and vincristine exposure and defects in murine DNA repair, which enhance the toxic effects of cisplatin [4,5]. Also, certain mitochondrial RNA gene defects predispose to familial aminoglycoside-induced deafness [6].…”
Section: Introductionmentioning
confidence: 99%